Standart for the capacity of Kos amphorae IV – I centuries BC - Abrosimov, Eduard Nikolaevich; Glyadelov, Vladimir Vladimirovich (Античный мир и археология, 2022)
The article describes a method for calculating the volume of amphorae using the three-dimensional editor Blender and proposes a new fairly accurate method for calculating the volume of antique amphorae on the example of transport amphorae of the Kos island IV–I century BC. The method described in the article is based on the 3-D model of amphorae as complex bodies of revolution. The creation of an effective 3-D model of a transport amphora proves the fundamental possibility of creating similar mathematical models for amphorae in other antique centers of winemaking and trade.